Carta del Director Mayo 2013 - Martínez Ventura, Jaime Edwin (Revista Policía y Seguridad Pública, 2013)
DOI: http://dx.doi.org/10.5377/rpsp.v2i0.1189 Revista Policía y Seguridad Pública 2(0) 2013: 15-17